2019
DOI: 10.1038/s41598-019-40945-4
|View full text |Cite
|
Sign up to set email alerts
|

High fabrication-tolerant narrowband perfect graphene absorber based on guided-mode resonance in distributed Bragg reflector

Abstract: We propose the narrowband perfect absorbers with enormously high fabrication tolerance, which consists of a low-contrast grating and a finite distributed Bragg reflector (DBR) layer with an ultrathin absorbing medium (graphene). It is numerically shown that the proposed perfect absorber outperforms the previously proposed schemes in fabrication tolerance. According to the rigorous coupled wave analysis (RCWA) and coupled mode theory (CMT) fitting, over a considerably wide range of grating width and thickness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…1(a)) consists of a prism ( n 1 ), a cavity layer ( n 2 ), air ( n 3 ), and monolayer graphene embedded in the cavity layer, where n 1 > n 2 > n 3 = 1. For the permittivity of graphene, Kubo formulation was used with parameters of a graphene thickness of 0.34 nm, Fermi level of 0 eV (undoped), Fermi velocity of 10 6 m/s, and mobility of 0.5 m 2 /Vs 29,30 . In this work, BK7 glass and PDMS are used as the prism and the cavity layer, respectively, unless otherwise stated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1(a)) consists of a prism ( n 1 ), a cavity layer ( n 2 ), air ( n 3 ), and monolayer graphene embedded in the cavity layer, where n 1 > n 2 > n 3 = 1. For the permittivity of graphene, Kubo formulation was used with parameters of a graphene thickness of 0.34 nm, Fermi level of 0 eV (undoped), Fermi velocity of 10 6 m/s, and mobility of 0.5 m 2 /Vs 29,30 . In this work, BK7 glass and PDMS are used as the prism and the cavity layer, respectively, unless otherwise stated.…”
Section: Resultsmentioning
confidence: 99%
“…To numerically investigate and analyze the reflection phase and absorption properties in the proposed perfect absorber, we used the TMM 33,34 . In all our calculations, the complex permittivity of graphene ( ε g ) was calculated using Kubo formulation based on the local random phase approximation for various E f , assuming graphene thickness of 0.34 nm, Fermi velocity of 10 6 m/s, and mobility of 0.5 m 2 /Vs 29,30 .…”
Section: Methodsmentioning
confidence: 99%
“…From (2), it is found that perfect absorption ( r = t = 0) is obtained only when , which implies the balance between the loss rate and the total leakage (coupling to the propagation channel) rate in each resonator and is the same as the critical coupling (perfect absorption) condition in the lossy one-port resonator with a reflector 38 . So, the perfect absorber based on the lossy all-pass filter can be understood as the variation of the lossy one-port resonator-based perfect absorber: the reflector is eliminated by placing another identical resonator with a mirror inversion symmetry.…”
Section: Resultsmentioning
confidence: 99%
“…Another method is to use periodic metal units to excite surface plasmon polaritons to enhance the absorption of graphene [16][17][18][19][20][21]. In addition, periodic multi-layer dielectric materials have also been reported to enhance the absorption of graphene based on optical resonance effect [22][23][24][25][26]. These achievements open up a new way for designing graphene-based absorbers.…”
Section: Introductionmentioning
confidence: 99%